Presidential Address: Corporate Finance and Reality - GRAHAM, JOHN R. (Journal of Finance, 2022)
ABSTRACT This paper uses surveys to document CFO perspectives on corporate planning, investment, capital structure, payout, and shareholder versus stakeholder focus. Comparing policy decisions today to those 20 years ago, I find that companies employ decision rules that are conservative, sticky, and geared to time the market; rely on internal forecasts that are miscalibrated and considered reliable only two years ahead; and emphasize corporate objectives that focus increasingly on stakeholders and revenues. These practice of corporate finance themes can discipline academic models toward better explaining outcomes. Models of satisficing decision‐making or costly managerial biases align with many of the themes.